Know your neighbor : Tom Murphy (The Raton Daily Range Raton, New Mexico, 1964)
Newspaper Article on Tom Murphy and his life.
Master list item #: 11
File location is in the Raton File Cabinet
Keywords: Murphy, Tom; Moore, Eugene; Murphy, Michael James; Hubbard, L. A; Errington, J.J.; Jolson, Al; McKenna, Bernard; Slee, Mabel; Murphy, Frances; Shuler Theatre; Raton HIgh School; University of New Mexico; Modern Electric; El Rialto; Hubbard - Murphy Inc; Gilralter Eenterprises; New Mexico Theatre Owners Association; Warner Brothers; El Raton; Local History; Biography; Life and Customs; Education; Business; Entertainment; Theatre; Raton, New Mexico; Denver, Colorado; Clayton, New Mexico; Alamosa, Colorado; Del Norte, Colorado